EnantioselectivePhotolysis and Quantitative Chiral Analysis of Tryptophan Complexed With Alkali‐Metalized L‐Serine in the Gas Phase. Issue 5 (1st April 2015) - Fujihara, Akimasa; Maeda, Naoto; Hayakawa, Shigeo
Abstract The enantioselectivephotolysis of a cold gas‐phase noncovalent complex of tryptophan with alkali‐metalized L‐serine, M+(L‐Ser)(Trp) (M = Na and Li), was examined using a tandem mass spectrometer containing a variable‐temperature ion trap. CO2 loss from Trp in the clusters was enantiomerically selective in ultraviolet excitation with linearly polarized light. M+(L‐Ser) promoted the enantioselectivephotolysis of Trp as a chiral auxiliary. The enantioselectivephotolysis of the D‐enantiomer was applied to a quantitative chiral analysis, in which the optical purity of tryptophan could be determined by measuring the relative abundance ratio R of the enantioselective CO2 loss to the chiral‐independent evaporation of L‐Ser in a single photodissociation mass spectrum of M+(L‐Ser)(Trp). Chirality 27:349–352, 2015. © 2015 Wiley Periodicals, Inc.